Diagnostic performance of transient elastography in differentiation between porto‐sinusoidal vascular liver disease and compensated cirrhosis - Zhang, Guanhua; Ma, Lin; Fu, Li; Li, Min; He, Fuliang; Feng, Lijuan; Wang, Min; Jia, Jidong; Wang, Yu; Zhao, Xinyan (Liver international, 2023)
Background and AimsThe efficacy of transient elastography (TE) in the differential diagnosis between porto‐sinusoidal vascular disease (PSVD) and compensated cirrhosis has not been sufficiently studied. We aimed to investigate the diagnostic performance of TE and identify histological lesions associated with liver stiffness.MethodsWe conducted a retrospective cohort study including patients with PSVD and cirrhosis (Child‐Turcotte‐Pugh class A) and healthy subjects. Both the PSVD and cirrhotic patients had at least one sign of PH. The area under the receiver operating characteristic curve (AUROC) was used for differentiation.ResultsNinety‐two patients with PSVD (median age: 53 years, 33% male), 100 patients with compensated cirrhosis and 101 healthy subjects were included. The median TE‐LSM in the PSVD patients (10.0 [7.0–13.0] kPa) was significantly lower than that in the cirrhotic patients (21.0 [15.0–28.0] kPa, p < .001) but was significantly higher than that in the healthy subjects (5.1 [4.6–6.0] kPa, p < .001). The AUROCs of TE‐LSM for the discrimination of PSVD from the cirrhosis and healthy subjects were 0.886 (95% CI: 0.833–0.928) and 0.913 (95% CI: 0.864–0.949), respectively. The sensitivity and specificity to discriminate PSVD from compensated cirrhosis were 78.3% and 82.0%, respectively, at a cut‐off of 13.6 kPa. Furthermore, portal fibrosis and aberrant cytokeratin 7 expression of centrilobular hepatocytes were significantly associated with higher TE‐LSM (≥10.0 kPa).ConclusionTE‐LSM can be used to differentiate PSVD from compensated cirrhosis. Pathological features in association with increased liver stiffness are identified.